Anti-IH in myelodysplastic syndrome - Ketsaraporn Wongba; Pornlada Nuchnoi; Chotiros Plabplueng; Charuporn Promwong (Practical Laboratory Medicine)
Background: Anti-IH exhibits complex specificity, strongly reacting with cells expressing both H and I antigens at cold temperatures. Its clinical significance has been increasingly recognized, particularly in patients with hematologic conditions such as myelodysplastic syndrome (MDS) and chronic myelomonocytic leukemia (CMML). Case report: We present an 83-year-old Thai female with MDS who was transfusion-dependent. She presented with severe anemia requiring an urgent transfusion. The patient was group A RhD-positive. Antibody screening and identification using column agglutination technology (CAT) showed weak polyagglutination. Auto-control and direct antiglobulin tests (DAT) were negative. Red cell typing showed absence of H antigen and presence of A1 antigen. Further testing with cord O cells revealed no agglutination, confirming the A1 blood group with anti-IH. Antibody screening and identification studies showed cold-reactivity, with weak reactivity at 37 °C and in the AHG phase. Crossmatching with two group A leukocyte-poor red cells was compatible, and transfusion was uneventful. Conclusion: This is the first reported case of anti-IH in a Thai patient. Anti-IH may complicate pre-transfusion testing and mask alloantibodies, necessitating careful interpretation and confirmatory testing to prevent transfusion-related complications.